A BRIEF GRAMMAR OF THE EASTERN ATADEI LANGUAGE OF LEMBATA, INDONESIA - Krauße, Daniel (Masyarakat Linguistik Indonesia, 2016)
This paper aims to briefly describe the grammar of Atadei, or more precisely Eastern Atadei, an under-described Flores-Lembata language spoken by about 8,000 people in Atadei District of Lembata, East Nusa Tenggara, Indonesia. Atadei is an agglutinative language with fusional elements and SVO word order. Adjectives follow the noun they modify and are inflected in attributive position, but are not inflected when used as a predicative. Atadei verbs may agree with the subject, depending on the verb class. This is similar to Lamaholot, but the verb classes in these two languages are different. Some verbs exhibit inflection for all persons, while others do not inflect at all. Pronouns follow a complex system in Atadei, depending on their syntactic function. It is noteworthy that the Alor-Pantar languages of the neighboring islands Alor and Pantar do not belong to the Austronesian language family, and may have contributed to a Papuan substratum in Atadei, such as inalienable possession and clause-final negation (Klamer et al., 2008, p. 136).